Implementasi Media Pembelajaran Aplikasi 25 Kisah Nabi dan Rasul untuk Peningkatan Hasil Belajar Akidah - Munir, Wahyuni; Munir, Humaerah; Munir, Nilam Permatasari; Munir, Fairus Suryani (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2022)
Learning media is an important role in the learning process, especially during the learning period from home. Teachers try to maximize learning by utilizing various learning resources such as applications on the Playstore, namely 25 stories of prophets and apostles. The purpose of this research was to determine the increase in learning outcomes of moral aqidah through the application of Â 25 Stories of the Prophets and Apostles. This research was a class action research in odd semester 2020/2021 for class X MA DDI Taqwa Parepare as many as 17 students. The research instrument was a test of moral aqidah learning outcomes, observation sheets, and student responses. Analysis of the data used is descriptive average statistic. The result of this research is Â that students' activities when using learning media in the first cycle are in the active category and the second cycle is in the very active category. The learning outcomes of students' moral aqidah in the first cycle of 61.75 are in the good category, and the learning outcomes in the second cycle of 83.25 are in the very good category. Students responded positively to the learning media for the stories of 25 Prophets and Apostles.